The synergy between the government and the society for sustainable sanitation - Sarfefa, Ismael; Rengkung, Wempi; Wurarah, Rully Novie (Institute for Advanced Science Social, and Sustainable Future, 2024)
Background: Ensuring sufficient and enduring sanitation is crucial for the progress of the community, particularly in Ransiki, where obstacles exist in terms of public involvement and infrastructure. This study examines different strategies for enhancing the quality of housing and sanitation through partnerships between communities and local governments. The process comprises a comprehensive field survey and a thorough interview using a predetermined set of questions. Methods: The data analysis conducted using the Smart PLS approach revealed that the community-based sanitation system in Ransiki was unsuccessful in enhancing the quality of settlements. Result: The primary issue lies in the insufficient sanitary infrastructure and the lack of public sanitation awareness. Establishing sanitation in the courtyard and surrounding regions is the only way to enhance the quality of human resources and settlements. Public engagement in sanitation remains limited, primarily due to insufficient education. While local governments prioritize infrastructure development, such as waste management and TPA, they must broaden their focus to include other areas, such as sanitation education. Moreover, the study revealed that the quality of settlements is directly influenced by factors such as the home environment, household hygiene, and human resources. Enhanced human resources positively impact the use of clean and safe water. Conclussion: This study asserts that improved collaboration between community and government endeavors is vital. Enhancing sanitation in a successful and enduring manner necessitates heightened public consciousness and education regarding sanitation, as well as government policies that are receptive and proactive. This study offers valuable perspectives on constructing efficient and enduring sanitation initiatives in Ransiki and other locations facing comparable circumstances.